A new water culture?: institutional inertia and technocratic water management in Peru - French, Adam (2016)
The 2009 Hydrologic Resources Law (Law 29338) shifted the legal and institutional framework in Peru’s water sector toward a focus on Integrated Water Resource Management (IWRM). This change formally ended the explicit prioritization of water for agricultural uses that had prevailed for four decades under the prior legal regime enacted during the nation’s agrarian reform. This article combines analysis of Peru’s current legal and institutional setting for water management with examination of the historical dynamics betweenthe state water bureaucracy and Peruvian society to argue that the existing arrangements for water governance reflect the enduring influence of an engineer-led technocracy rooted in the high-modernist approaches of the 20th century. The article illustrates how the state bureaucracy has consolidated centralized authority over the water sector through assimilation and adaptation of the IWRM paradigm and the development of a water regime that prioritizesthe formalization of water rights, recognition of the economic value of water, and water-use efficiency.